Extended Endoscopic Endonasal Approach for Craniopharyngioma Removal - Messerer, Mahmoud; Maduri, Rodolfo; Daniel, Roy Thomas (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objective Endoscopic transsphenoidal extended endoscopic approach (EEA) represents a valid alternative to microsurgery for craniopharyngiomas removal, especially for retrochiasmatic lesions without large parasellar extension. The present video illustrates the salient surgical steps of the EEA for craniopahryngioma removal.Patient A 52-year-old man presented with a bitemporal hemianopia and a bilateral decreased visual acuity. MRI showed a Kassam type III cystic craniopharyngioma with a solid component (Fig. 1, panels A and B).Surgical Procedure The head is rotated 10 degrees toward the surgeons. The nasal step is started through the left nostril with a middle turbinectomy. A nasoseptal flap is harvested and positioned in the left choana. The binostril approach allows a large sphenoidotomy to expose the key anatomic landmarks. The craniotomy boundaries are the planum sphenoidale superiorly, the median opticocarotid recesses, the internal carotid artery laterally and the clival recess inferiorly. After dural opening and superior intercavernous sinus coagulation, the tumor is entirely removed (Fig. 2, panels A and B). Skull base reconstruction is ensured by fascia lata grafting and nasoseptal flap positioning.Results Postoperative MRI showed the complete tumor resection (Fig. 1, panels C and D). At 3 months postoperatively, the bitemporal hemianopia regressed and the visual acuity improved. A novel left homonymous hemianopia developed secondary to optic tract manipulation.Conclusions The extended EEA is a valid surgical approach for craniopharyngioma resection. A comprehensive knowledge of the sellar and parasellar anatomy is mandatory for safe tumor removal with decreased morbidity and satisfactory oncologic results.The link to the video can be found at: https://youtu.be/NrCPPnVK2qA.
Keywords: craniopharyngioma; extended endonasal approach; endoscopy; parasellar lesions; transsphenoidal surgery